Preliminary study of pneumonia symptoms detection method using cellular neural network - Azian Azamimi, Abdullah; Norafifah, Md Posdzi; Nishio, Yoshifumi (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/